Strategi Guru dalam Implementasi Nilai Kearifan Lokal pada Proses Pembelajaran di SMA Negeri 5 Surakarta - Dwi Astutik; Shuha Osmana Azizah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Education is the main foundation to be able to create a good next generation of the nation. Furthermore, education based on local wisdom is also one of the efforts made so that students do not forget the cultural values ​​that exist around their place of residence. This study aims to see how the strategies applied by teachers in implementing local wisdom values ​​in the learning process at SMA Negeri 5 Surakarta also factors that encourage and hinder its implementation. This study was written using a qualitative research method with a case study approach. Samples were taken using a purposive sampling technique, namely teachers of sociology, history, Javanese language, PPKn, guidance and counseling, vice principal of the school for curriculum, and vice principal of student affairs. The results of this study found that various strategies have been applied by teachers at SMA Negeri 5 Surakarta to instill local wisdom values ​​in the learning process. These strategies aim to instill the values ​​of discipline, cooperation, ethics, and so on. There are several encouraging factors such as the P5 program, while inhibiting factors include the high use of cellphones among students. This study was analyzed using Max Weber's theory of social action, where students' social actions are influenced by their social environment and goals.